Pelatihan Peraturan Pemerintah No 20/2026 Untuk Wajib Pajak Orang Pribadi Dan Usaha Kecil Dan Menengah - Susanna Hartanto (CV. Multi Kreasi Media, 2026)
This tax training aims to improve tax knowledge and understanding for individual taxpayers and small and medium enterprises. This activity was motivated by the situation where many small and medium enterprises in the East Java I Directorate General of Taxes area still do not understand and apply the latest tax regulations correctly and completely, namely Government Regulation Number 20 of 2026 concerning Amendments to Government Regulation Number 55 of 2022 concerning Adjustments in the Income Tax Sector. This training explains how to impose income tax on business income received or obtained by individual taxpayers and corporate entities in the form of sole proprietorships and cooperatives that have a certain gross income. The training activity was conducted online, and training materials were provided to participants in PowerPoint format. The methods used in implementing this activity consisted of preparation, implementation, and evaluation. Pre- and post-tests were conducted to determine the increase in knowledge and understanding of webinar participants. Overall, taxpayers who are individuals and small and medium enterprises felt helped in gaining knowledge and understanding of the latest tax regulations and were able to apply the latest regulations in paying income tax and reporting Income Tax Return (SPT) correctly and completely.